Corporate Governance among Small and Medium Size Enterprises in Algeria: “Impediments to the Practice of Corporate Governance System” - Brahim, Zerrouki; Nourredine, Fellag (Asian Journal of Economic Modelling, 2017)
This study aims to shed light on the fact of corporate governance in the Algerian small and medium size enterprises where the intention is to identify and make the point over the fact of corporate governance in Algerian joint-stock enterprises, so as to state the major and essential obstacles that stand against the good practice of corporate governance. The study took place in 4 joint-stock enterprises in the region of CHLEF, the empirical study was about a questionnaire in which we tried to recognize the fact of corporate governance of these stated companies and to pull out the different problems that impedes the enterprises path toward the good development. However, our reached results were that the corporate governance concept is not enabled as it should be and the Algerian small and medium enterprise suffers from lot of problems in which initially the family nature and successions problems, also the relation between the main actor’s elements is not good and the legal and organizational environment is not encouraging.